Efficient sub-15 nm cubic-phase core/shell upconversion nanoparticles as reporters for ensemble and single particle studies. Issue 19 (6th May 2020) - Tan, Meiling; Monks, Melissa-Jane; Huang, Dingxin; Meng, Yongjun; Chen, Xuewen; Zhou, Ying; Lim, Shuang-Fang; Würth, Christian; Resch-Genger, Ute; Chen, Guanying
Abstract : A set of sub-15 nm ytterbium-enriched α-NaYbF4 :Er 3+ @CaF2 core/shell upconversion nanoparticles have been developed for both ensemble- and single particle-level imaging studies, presenting a high quantum yield of 0.77% at a low saturation power density of 110 W cm −2 . Abstract : Single particle imaging of upconversion nanoparticles (UCNPs) has typically been realized using hexagonal (β) phase lanthanide-doped sodium yttrium fluoride (NaYF4 ) materials, the upconversion luminescence (UCL) of which saturates at power densities ( P ) of several hundred W cm −2 under 980 nm near-infrared (NIR) excitation. Cubic (α) phase UCNPs have been mostly neglected because of their commonly observed lower UCL efficiency at comparable P in ensemble level studies. Here, we describe a set of sub-15 nm ytterbium-enriched α-NaYbF4 :Er 3+ @CaF2 core/shell UCNPs doped with varying Er 3+ concentrations (5–25%), studied over a wide P range of ∼8–10 5 W cm −2, which emit intense UCL even at a low P of 10 W cm −2 and also saturate at relatively low P . The highest upconversion quantum yield ( Φ UC ) and the highest particle brightness were obtained for an Er 3+ dopant concentration of 12%, reaching the highest Φ UC of 0.77% at a saturation power density ( P sat ) of 110 W cm −2 . These 12%Er 3+ -doped core/shell UCNPs were also the brightest UCNPs among this series under microscopic conditions at high P of ∼10 2 –10 5 W cm −2 as demonstrated by imaging studies at the single particle level. Our results underline the potential applicability of the described sub-15 nm cubic-phase core/shell UCNPs for ensemble- and single particle-level bioimaging.